2009
DOI: 10.1182/blood-2008-12-192294
|View full text |Cite
|
Sign up to set email alerts
|

EphrinB reverse signaling contributes to endothelial and mural cell assembly into vascular structures

Abstract: EphrinB transmembrane ligands and their cognate EphB receptor tyrosine kinases regulate vascular development through bidirectional cell-to-cell signaling, but little is known about the role of EphrinB during postnatal vascular remodeling. We report that EphrinB is a critical mediator of postnatal pericyte-to-endothelial cell assembly into vascular structures. This function is dependent upon extracellular matrixsupported cell-to-cell contact, engagement of EphrinB by EphB receptors expressed on another cell, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
122
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(125 citation statements)
references
References 51 publications
3
122
0
Order By: Relevance
“…More recently, Salvucci et al (2009) reported that Eph-B is a critical mediator of postnatal pericyte to endothelial cell assembly into vascular tubes. Furthermore, inhibition of Eph-B activity prevents assembly of pericytes and endothelial cells.…”
Section: Ephrins and Eph Receptorsmentioning
confidence: 99%
“…More recently, Salvucci et al (2009) reported that Eph-B is a critical mediator of postnatal pericyte to endothelial cell assembly into vascular tubes. Furthermore, inhibition of Eph-B activity prevents assembly of pericytes and endothelial cells.…”
Section: Ephrins and Eph Receptorsmentioning
confidence: 99%
“…7B). Additionally, recent data have implicated a role for EphB-ephrin-B signaling in the assembly of endothelial and mural cells into vascular structures (Salvucci et al, 2009) and also in the adhesion and migration of monocytes on endothelial cells (Pfaff et al, 2008).…”
Section: Ephrin-b2 Expression Regulates Cell Motilitymentioning
confidence: 99%
“…In adult mice, ephrinB has been reported to be phosphorylated and activated in ECs and pericytes in wounded skin of mice. 17 However, there are no studies investigating the role of ephrinB2 reverse signaling in angiogenesis and fibrosis after tissue injury in adults. We therefore investigated the role of ephrinB2 signaling in the kidney after injury.…”
mentioning
confidence: 99%